Use of Prospective Multiplex Immunohistochemistry to Redefine Tissue Pathways of Diagnostic Core Biopsy of Prostate. Issue 9 (6th October 2022) - Thomas, Teresa; Wedden, Sarah; Afzal, Naveed; Mikel, John; D'Arrigo, Corrado
Abstract : The incidence of prostatic cancer in the United Kingdom has increased over 40% in the past 30 years. The majority of these cancers are diagnosed by core biopsy, posing a considerable strain on a service that struggles to recruit sufficient histopathologists. The current methodology for tissue diagnosis has a significant false-negative rate, small false-positive rate, and a proportion of indeterminate diagnoses. Therefore, this area presents an opportunity both to improve diagnostic quality and to reduce the burden on resources. We investigated streamlining tissue pathways by increasing the utilization of readily available resources to reduce the burden on scarce resources and improve the accuracy of diagnosis. This involved applying prospective multiplex immunohistochemistry (IHC) using 4 different markers (CK5, p63, racemase, and Ki-67) and 2 chromogens. We conducted a prospective study using over 8000 cores and 3 consultant histopathologists. The pathologists assessed each core using either conventional stains (hematoxylin and eosin) only or multiplex IHC only. The results of this assessment were later compared with the overall assessment made for the final histologic diagnosis. Results show that IHC alone has a positive predictive value of 98.97% and a negative predictive value of 99.91%, while hematoxylin and eosin alone has a positive predictive value of 94.21% and negative predictive value of 99.07%, demonstrating improved diagnostic accuracy. When assessed against the use of on-demand IHC, prospective IHC improves turn-around-times, reduces indeterminate diagnoses, improves pathologist's accuracy and efficiency and, in overall terms, is cost-effective. In addition, it is possible to structure these tests within the routine of a diagnostic service with little impact on the overall capacity of the laboratory.